Self-Management Through Social Support Among Emerging Adults With Inflammatory Bowel Disease. Issue 4 (July 2019) - Kamp, Kendra J.; Luo, Zhehui; Holmstrom, Amanda; Given, Barbara; Wyatt, Gwen
Abstract : Background: Emerging adulthood is a unique developmental stage, which may affect individuals' self-management behaviors, social support, and the relationship between these two constructs. Among older adults, social support has been shown to improve self-management behaviors for individuals with chronic conditions; however, this relationship has not been examined with emerging adults (age 18–29 years) who have inflammatory bowel disease (IBD). Objectives: The aim of the study was to examine the relationship between two conceptualizations of social support (received and perceived availability of social support) and IBD-related self-management behaviors among emerging adults with IBD. Methods: A convenience sample of emerging adult IBD individuals (currently prescribed medication to manage IBD) were recruited through ResearchMatch, Facebook, and word of mouth. The study was guided by key elements of the individual and family self-management theory. Participants responded to demographic and condition-specific questionnaires: the Inventory of Dimensions of Emerging Adulthood, the Inventory of Socially Supportive Behaviors, the Medical Outcomes: Social Support Survey, the Medication Adherence Report Scale, and the Dietary Screener Questionnaire. Results: Emerging adults with high received informational support reported greater medication adherence compared to those with low received informational support when controlling for biological medications, time since diagnosis, symptom frequency, and feeling in-between adolescence and adulthood. Neither type of social support was associated with diet modification. Discussion: Received informational social support, medication type, time since diagnosis, symptoms, and emerging adulthood factors have the potential to influence medication adherence. Received informational social support interventions, such as patient-to-patient or group-based mentoring, may serve to improve medication adherence among emerging adults with IBD. Abstract : Supplemental digital content is available in the text.